Video recruitment as a tool for building an attractive employer brand – the perspective of Generation Z - Gryko, Arkadiusz (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
The rapid development of digital technologies is revolutionizing not only the way we work, but also how we look for work. Recruitment and selection processes, once based on traditional methods, are undergoing dynamic changes, becoming increasingly virtual. This is particularly evident in the context of Generation Z, which is entering the labor market in an era of digital dominance. This article aims to analyze the impact of video recruitment on employer branding in the context of the expectations and experiences of Generation Z. To this end, desk research and quantitative research were conducted on a deliberately selected group (n=192) of representatives of this generation who have recruitment experience. The results of the study show that the form of communication in the recruitment process influences not only the subjective feelings of candidates about the recruitment itself, but also the way they interpret the attitude of a potential employer and the characteristics they attribute to them, which has implications for the employer's image. The way candidates perceive an employer's brand depends both on their individual characteristics and recruitment experiences, as well as their expectations of the employer.